Bothrops leucurus venom induces nephrotoxicity in the isolated perfused kidney and cultured renal tubular epithelia - de Morais, Isabel Cristina Oliveira; Torres, Alba Fabíola Costa; Pereira, Gustavo José da Silva; Pereira, Ticiana Praciano; Pessoa Bezerra de Menezes, Ramon Róseo de Paula; Mello, Clarissa Perdigão; Coelho Jorge, Antonio Rafael; Bindá, Alexandre Havt; Toyama, Marcos Hikari [UNESP]; Monteiro, Helena Serra Azul; Smaili, Soraya Soubhi; Martins, Alice Maria Costa (Elsevier, 2013)
Bites from snake (Bothrops genus) cause local tissue damage and systemic complications, which include alterations such as hemostatic system and acute renal failure (ARF). Recent studies suggest that ARF pathogenesis in snakebite envenomation is multifactorial and involves hemodynamic disturbances, immunologic reactions and direct nephrotoxicity. The aim of the work was to investigate the effects of the Bothrops leucurus venom (BlV) in the renal perfusion system and in cultured renal tubular cells of the type MDCK (Madin-Darby Canine kidney). BlV (10 μg/mL) reduced the perfusion pressure at 90 and 120 min. The renal vascular resistance (RVR) decreased at 120 min of perfusion. The effect on urinary flow (UF) and glomerular filtration rate (GFR) started 30 min after BlV infusion, was transient and returned to normal at 120 min of perfusion. It was also observed a decrease on percentual tubular transport of sodium (%TNa+) at 120 min and of chloride (%TCl-) at 60 and 90 min. The treatment with BlV caused decrease in cell viability to the lowest concentration tested with an IC50 of 1.25 μg/mL. Flow cytometry with annexin V and propidium iodide showed that cell death occurred predominantly by necrosis. However, a cell death process may involve apoptosis in lower concentrations. BlV treatment (1.25 μg/mL) led to significant depolarization of the mitochondrial membrane potential and, indeed, we found an increase in the expression of cell death genes in the lower concentrations tested. The venom also evoked an increase in the cytosolic Ca2+ in a concentration dependent manner, indicating that Ca2+ may participate in the venom of B. leucurus effect. The characterization of the effects in the isolated kidney and renal tubular cells gives strong evidences that the acute renal failure induced by this venom is a result of the direct nephrotoxicity which may involve the cell death mechanism. © 2012.
Keywords: Bothrops leucurus; Nephrotoxicity; Renal tubular epithelia; Bothrops leucurus venom; calcium ion; caspase 3; caspase 8; snake venom; unclassified drug; acute kidney failure; animal cell; animal experiment; animal model; Bothrops; cell death; cell viability; controlled study; cytotoxicity test; gene expression; glomerulus filtration rate; IC 50; kidney perfusion; kidney tubule cell; kidney vascular resistance; male; micturition; mitochondrial membrane potential; nephrotoxicity; nonhuman; perfusion pressure; priority journal; rat; sodium transport; Animals; Annexin A5; Apoptosis Regulatory Proteins; Calcium; Cell Survival; Cells, Cultured; Coloring Agents; Crotalid Venoms; Dogs; Epithelial Cells; Epithelium; Fluorescein-5-isothiocyanate; Fluorescent Dyes; Gene Expression; Kidney Diseases; Kidney Tubules; Male; Organ Culture Techniques; Propidium; Rats